2015
DOI: 10.1371/journal.pone.0123589
|View full text |Cite
|
Sign up to set email alerts
|

Underweight Full-Term Indian Neonates Show Differences in Umbilical Cord Blood Leukocyte Phenotype: A Cross-Sectional Study

Abstract: BackgroundWhile infections are a major cause of neonatal mortality in India even in full-term neonates, this is an especial problem in the large proportion (~20%) of neonates born underweight (or small-for-gestational-age; SGA). One potential contributory factor for this susceptibility is the possibility that immune system maturation may be affected along with intrauterine growth retardation.MethodsIn order to examine the possibility that differences in immune status may underlie the susceptibility of SGA neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…On the other hand, siblings were far similar to each other in memory subset frequencies than non-siblings were, suggesting a hereditary component or shared environmental factors in regulating memory lymphocyte frequencies. Any similarity between siblings could be attributed to early life influences, since it is well recognized that both intra-uterine [49,50] and neonatal [51] stress impacts immune system development, and a recent study [13] has shown a prominent role for co-habitation in determining immune phenotypes. Our findings are consistent with two previous studies [1,14] which report high degree of heritability for majority of immune subsets.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, siblings were far similar to each other in memory subset frequencies than non-siblings were, suggesting a hereditary component or shared environmental factors in regulating memory lymphocyte frequencies. Any similarity between siblings could be attributed to early life influences, since it is well recognized that both intra-uterine [49,50] and neonatal [51] stress impacts immune system development, and a recent study [13] has shown a prominent role for co-habitation in determining immune phenotypes. Our findings are consistent with two previous studies [1,14] which report high degree of heritability for majority of immune subsets.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adult individuals, the frequency of classical monocytes varies from 80 to 90% of total monocytes. On the other hand, nonclassical monocytes constitute about 8-10%, whereas neonates have a low number of nonclassical monocytes [8, 9]. The phenotype and function of monocyte subsets change extensively in inflammatory disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this hypothesis, an increased risk of infections and aberrant immune development has been reported in both preterm [ 14 26 ] and SGA infants [ 27 28 29 30 ].…”
Section: Discussionmentioning
confidence: 71%